Secure Remote (Home) Electronic Exam Systems: Features, Challenges, and Development of an Offline Model - Keyamo, Clement Amone; Adebukola, Onashoga Saidat; Baale, Abimbola Adebisi (IJIE (Indonesian Journal of Informatics Education), 2024)
The development of e-assessment systems that can meet acceptable standards in the education industry is a present focus of researchers in the distance learning area. Cheating  and impersonation in online examinations are two common challenges that  have spawned diverse solutions that are usually based on continuous authentication and monitoring principles and technologies. Most of the solutions are focused on centralized e-proctoring schemes that depend massively on state-of the-art internet connectivity. However, many users of these systems, especially in the developing countries, have limited internet services. This is a major barrier to effective remote e-assessment of learners as many of these solutions fail with failing internet services.  To resolve this challenge, this paper describes a Secure Offline  Continuous  Authentication and Monitoring(SOCAM) model for remote e-assessment.